Cladless few mode fiber grating sensor for simultaneous refractive index and temperature measurement - Yang, H.Z.; Ali, M.M.; Islam, M.R.; Lim, Kok Sing; Gunawardena, D.S.; Ahmad, Harith (Elsevier, 2015)
In this work, we have demonstrated a cladless few-mode fiber grating sensor for simultaneous measurement of refractive index (RI) and temperature. The proposed sensor is fabricated from an etched few-mode Fiber Bragg Grating (FMFBG) that can support two Bragg wavelengths, in which the sensitivities for each Bragg wavelength to the changes of RI and temperature are different. A mode coupling theory is used to describe the sensing principle of the proposed sensor and the simulation result finding that an etched diameter of 14.1 μm can get the better performance for optimal the power confinement of etched FMFBG. Experimental results show that the proposed sensor has the RI sensitivities for both λ01 and λ11 are estimated to be 1.183 nm/RIU and 4.816 nm/RIU respectively, and temperature sensitivities for λ01 and λ11 are 9.62 ± 0.08 pm/°C and 9.52 ± 0.13 pm/°C respectively. With the assistance of 3 × 3 characteristic matrix, discrimination measurements of temperature and RI has been demonstrated and the deviations in RI and temperature measurements are ±8 × 10-4 RIU and ±1 °C respectively.